Multimodality Reflected in EFL Teaching Materials: Indonesian EFL In-Service Teacher’s Multimodality Literacy Perception - Trisanti, Novia; Suherdi, Didi; Sukyadi, Didi (Language Circle: Journal of Language and Literature, 2022)
The digital age, which has impacted EFL teaching and learning in Indonesia, has compelled educators to uphold higher instruction standards. Multimodality is currently an updated topic in relation to digital media in EFL learning. This study intends to examine the effects of Indonesian EFL teachers' multimodality perceptions in the teaching materials. It clarifies how EFL teachers in secondary schools use multimodal literacy practices for their students to develop learner’s critical thinking and creativity. A mixed method with an explanatory sequential design was employed, with quantitative data analysis serving as the primary source of support for the results of the qualitative analysis. This study included 38 EFL in-service teachers in Indonesia. Open and close-ended questionnaires with score measurements as well as interviews regarding the multimodal structure expression, content, and preference were used to gather the data. The findings of the participants’ multimodal literacy reveal a respectable mean score of 71.4 and standard deviation of 11. The questionnaire analysis results indicate that utilizing elements of visual (real images), auditory, and written elements is helpful in explaining the teaching and learning materials to the learners and can ensure that they have a thorough understanding of the materials using multimodal expression, content and preference. Overall, this shows that Indonesian EFL in-service teachers have shown adaptability in implementing multimodal literacy in their instructional materials, and they are conscious of switching from traditional to digital mode. As a result, more research is required to investigate the multimodal literacy practices used by EFL teachers in Indonesia